Effects of obesity on lung volume and capacity in children and adolescents: a systematic review - Aline Dill Winck; João Paulo Heinzmann-Filho; Rafaela Borges Soares; Juliana Severo da Silva; Cristhiele Taís Woszezenki; Letiane Bueno Zanatta
Abstract Objective: To assess the effects of obesity on lung volume and capacity in children and adolescents. Data source: This is a systematic review, carried out in Pubmed, Lilacs, Scielo and PEDro databases, using the following Keywords: Plethysmography; Whole Body OR Lung Volume Measurements OR Total Lung Capacity OR Functional Residual Capacity OR Residual Volume AND Obesity. Observational studies or clinical trials that assessed the effects of obesity on lung volume and capacity in children and adolescents (0-18 years) without any other associated disease; in English; Portuguese and Spanish languages were selected. Methodological quality was assessed by the Agency for Healthcare Research and Quality. Data synthesis: Of the 1,030 articles, only four were included in the review. The studies amounted to 548 participants, predominantly males, with sample size ranging from 45 to 327 individuals. 100% of the studies evaluated nutritional status through BMI (z-score) and 50.0% reported the data on abdominal circumference. All demonstrated that obesity causes negative effects on lung volume and capacity, causing a reduction mainly in functional residual capacity in 75.0% of the studies; in the expiratory reserve volume in 50.0% and in the residual volume in 25.0%. The methodological quality ranged from moderate to high, with 75.0% of the studies classified as having high methodological quality. Conclusions: Obesity causes deleterious effects on lung volume and capacity in children and adolescents, mainly by reducing functional residual capacity, expiratory reserve volume and residual volume.